A Bayesian incentive compatible mechanism for fair division - Yuji Fujinaka (Osaka University, Institute of Social and Economic Research (ISER), 2008)
We consider the problem of fairly allocating one indivisible object when monetary transfers are possible, and examine the existence of Bayesian incentive compatible mechanisms to solve the problem. We propose a mechanism that satisfies envy-freeness, budget balancedness, and Bayesian incentive compatibility. Further, we establish the uniqueness of the mechanism under an order additivity condition. This result contrasts well with various results on the incompatibility between efficiency and ex post incentive compatibility.
Keywords: C72; C78; D61; D63; D71; 330; Bayesian incentive compatibility; Fair division; Indivisible good; Mechanism design